LOS EFECTOS DEL SISTEMA DE EVALUACION Y ACREDITACION DE LOS APRENDIZAJES N LOS ESTUDIANTES DEL OCTAVO, NOVENO Y DECIMO AÑO DE EDUCACION BASICA DEL INSTITUTO SUPERIOR TECNOLOGICO BABAHOYO EN EL PERIODO LECTIVO 2004-2005. - CELIA CRUZ LOPEZ (2006)
THE EFFECTS OF THE LEARNING EVALUATION AND ACCREDITATION SYSTEM ON STUDENTS IN THE EIGHTH, NINTH AND TENTH YEAR OF BASIC EDUCATION AT THE BABAHOYO HIGHER INSTITUTE OF TECHNOLOGY IN THE 2004-2005 SCHOOL PERIOD.